Innovative corporate performance management five key principles to accelerate results - Paladino, Bob, 1959- (Hoboken, N.J. : Wiley, 2011)
"Award-winning strategies to drive game changing meaningful results during the most challenging economy in decades Drawing from executive and thought leader Bob Paladino's research and advisory experiences and collaboration with award-winning and high-performing organizations, this sequel his global best seller Innovative Corporate Performance Management: Five Key Principles to Accelerate Results provides a clear road map for executing enterprise strategy. Reveals a proven implementation model that has accelerated breakthrough results Shares over 40 new, innovative best practices common to Malcolm Baldrige, Balanced Scorecard Hall of Fame, Sterling quality, Fortune 100 Best, APQC, and Forbes award winners Provides a CPM Process Blueprint and diagnostic to score your organization and establish a plan for your award winning performance Offers a fresh approach to integrating proven methodologies proven by case companies that have been awarded over 100 awards Includes key process maps, strategic planning frameworks, strategy maps, customer and competitor intelligence methods, balanced scorecards, comparative tables, project plans, testimonials, charts, graphs, and screen shots of CPM, CRM, BSC and KM systems. All-new case studies and best practice research are included from world-renowned enterprises as well as insights from executives who have won the most globally recognized awards in business."--
Machine generated contents note: Preface. -- Acknowledgments. -- Chapter 1: Introduction. -- Chapter 2: Research and New Case Company Results. -- Chapter 3: Five Key Principles of CPM: Best Practices Model. -- Chapter 4: Principle 1: Establish and Deploy a CPM Office and Officer. -- Chapter 5: Principle 2: Refresh and Communicate Strategy. -- Chapter 6: Principle 3: Cascade and Manage Strategy. -- Chapter 7: Principle 4: Improve Performance. -- Chapter 8: Principle 5: Manage and Leverage Knowledge. -- Chapter 9: Five Key Principles: Self-Diagnostic and Corporate. Performance Management Roadmap. -- Index.
Includes index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Organizational effectiveness; Management; Performance -- Case studies; Executives; Electronic books